2015
DOI: 10.6000/1929-5634.2015.04.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Test of Pyrroles in Psychiatric Disorders: Association with Nutritional, Immunological and Metabolic Markers

Abstract: Background: Psychiatrists started using urine pyrroles (hydroxyhemopyrrolin-2-one, HPL) to diagnose psychiatric disorders many years ago. The biological origins of HPL are not known, nor are the causes of elevated urinary pyrrole excretion well understood. Methods: In the present study we analyzed the level of pyrroles in 148 patients with schizophrenia, 135 patients with bipolar disorder, 97 patients with depression, 119 patients with ADHD and compared these data with the results of pyrrole tests for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
2
1
Order By: Relevance
“…This finding contradicts previous studies 5 , 25 , 27 , 28 , 37–42 that identify the urine component responsible for the Ehrlich’s mauve reaction as HPL. Interestingly, none of the previous studies used a pure, authentic HPL standard and so based their conclusions on a possible misinterpretation of the chemistry of the Ehrlich’s reaction.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding contradicts previous studies 5 , 25 , 27 , 28 , 37–42 that identify the urine component responsible for the Ehrlich’s mauve reaction as HPL. Interestingly, none of the previous studies used a pure, authentic HPL standard and so based their conclusions on a possible misinterpretation of the chemistry of the Ehrlich’s reaction.…”
Section: Resultscontrasting
confidence: 99%
“…A cross-sectional analysis of pyrroles in psychiatric disorders 28 suggested that there is a correlation between histamine levels and pyrrole levels. Histamine itself is unlikely to react with Ehrlich’s reagent as it does not have a free β-carbon.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated hydroxyhemopyrrolin-2-one (HPL) in urine has long been associated with psychiatric disorders, first recorded in schizophrenic patients, with similar findings regarding bipolar disorder, depression, hyperactivity disorder, Down Syndrome, and chronic fatigue syndrome [31,32]. Pyrrole (Figure 3), a precursor to HPL, is known to play a role in some biological pathways, including porphyrin synthesis for heme and cytochrome macromolecules.…”
Section: Discussionmentioning
confidence: 95%
“…Haeme porphyrin is then degraded by haeme oxidase in an oxidative process that is conjectured to contribute to urine excretion of the porphyrin pyrrole biomarker, hydroxypyrroline-2-one (HPL). High levels of this molecule have been detected in the urine of patients with schizophrenia and particularly in those who do not possess the homozygous MTHFR 677 polymorphism [81,126]. Elevated urine HPL levels are reportedly reduced by vitamin B6 (PLP) and zinc supplementation, though the exact mechanism of this effect is yet to be established [127].…”
Section: Discussionmentioning
confidence: 99%